Metabolism, infl ammation and postoperative time are the key to early diagnosis of anastomotic leak - Daniel T Jansson; Ioannis Oikonomakis; Ida E U Hall Strand; Adrian D Meehan; Kjell S Jansson (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Objective: The aim of the study was to fi nd laboratory samples for early diagnosis of anastomotic leak. Summary background data: Anastomotic leakage after rectal cancer surgery is a severe complication with high mortality. Outcome is highly dependent on early diagnosis. Methods: 29 patients were investigated postoperatively after having undergone low anterior resection due to cancer recti. Patient outcomes were divided into three groups: Anastomotic leak in 7 patients, other complications in 9 patients and 13 patients who were free of complications. Patients were monitored every 6th hour with blood and intraperitoneal samples in order to identify laboratory markers for early detection of anastomotic leakage. An anastomotic leak index was created, a scoring system where points count for values higher than reference values of CRP and interleukin 6 in blood and intraperitoneal lactate, lactate/ pyruvate ratio and interleukin 6 were measured at 18, 24, 42 and 48 hours postoperatively.